Local dominance - CATONINI, Emiliano (Institutional Knowledge at Singapore Management University, 2020)
We define a local notion of weak dominance that speaks to the true choice problems among actions in a game tree and does not necessarily require to plan optimally for the future. A strategy is (globally) weakly dominant if and only if it prescribes a locally weakly dominant action at every decision node it reaches, and in this case local weak dominance is characterized by a (wishful-thinking) condition that requires no forward planning. From this local perspective, we identify form of contingent reasoning that are particularly natural, despite the absence of an obviously dominant strategy (Li, 2017). Following this approach, we construct a dynamic game that implements the Top Trading Cycles allocation under a notion of local obvious dominance that captures a form of independence of irrelevant alternatives.